Acute Systemic Inflammation is Unlikely to Affect Adiponectin and Leptin Synthesis in Humans - Ekström, Mattias; Söderberg, Stefan; Tornvall, Per (Frontiers in Cardiovascular Medicine, 2015)
Adipose tissue, classically thought to be merely an energy store, has been shown to produce inflammatory and metabolically active cytokines. Recently, adiponectin and leptin, adipokines primarily synthesized by adipocytes, have attracted considerable attention because inflammation has been suggested to modulate adipokine levels. However, the regulation of adiponectin and leptin is complex and the knowledge about their synthesis within the early onset of inflammation is poorly understood. The aim of this study was to investigate if the synthesis of adiponectin and leptin is affected during the early phase of an acute systemic inflammation. Eighteen healthy subjects were allocated to vaccination against Salmonella Typhi or to a control group, and adiponectin and leptin concentrations measured in plasma during 24 hrs. Nine patients, without markers of inflammation, undergoing open heart surgery were investigated before and after the operation by analysis of plasma levels and adipose tissue gene expression of adiponectin and leptin. Plasma interleukin (IL)-6 concentrations were measured in both cohorts. Plasma levels of IL-6 were doubled after vaccination and increased 30-fold after open heart surgery. Plasma levels of adiponectin and leptin were unchanged after vaccination whereas adiponectin and leptin tended to decrease after surgery. The gene expression of adiponectin and leptin was unaltered in omental and subcutaneous adipose tissue after surgery. Despite the use of two models of stimulated in vivo systemic inflammation we found no evidence of an early regulation of adiponectin and leptin synthesis, indicating that these two adipokines are not key elements in an acute systemic inflammation in humans.